2017
DOI: 10.1039/c7ee01193h
|View full text |Cite
|
Sign up to set email alerts
|

Partial indium solubility induces chemical stability and colossal thermoelectric figure of merit in Cu2Se

Abstract: Thermoelectric figure of merit, ZT, exceeding 2.6 at 850 K and copper electromigration inhibition have been demonstrated in indium modified Cu2Se.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
217
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 296 publications
(227 citation statements)
references
References 43 publications
10
217
0
Order By: Relevance
“…Both Zhao et al and Liu et al have reported the peak zT value of SnSe can be higher than 2 when the temperature is above 800 K. Meanwhile, most other results suggest the peak zT values of SnSe are at the temperature range lower than 800 K . When the temperature is between ≈800 and ≈1000 K, Cu 2 X, PbX (X = Te, Se, and S), SnTe as well as low‐cost and stable BiCuSeO are more attractive. Through nonequilibrium processing, Tan et al have achieved a record‐high zT value of 2.5 in Pb 0.98 Na 0.02 Te‐8%SrTe at 923 K. As a potential substitution for highly toxic PbTe, peak zT values of SnTe of ≈1.5 have also been widely reported .…”
Section: Introductionmentioning
confidence: 98%
“…Both Zhao et al and Liu et al have reported the peak zT value of SnSe can be higher than 2 when the temperature is above 800 K. Meanwhile, most other results suggest the peak zT values of SnSe are at the temperature range lower than 800 K . When the temperature is between ≈800 and ≈1000 K, Cu 2 X, PbX (X = Te, Se, and S), SnTe as well as low‐cost and stable BiCuSeO are more attractive. Through nonequilibrium processing, Tan et al have achieved a record‐high zT value of 2.5 in Pb 0.98 Na 0.02 Te‐8%SrTe at 923 K. As a potential substitution for highly toxic PbTe, peak zT values of SnTe of ≈1.5 have also been widely reported .…”
Section: Introductionmentioning
confidence: 98%
“…Due to the high-degree homogeneously dispersed molecular CNTs inside the Cu 2 Se matrix, a zT of 2.4 at 1,000 K has been achieved. Olvera et al [22] reported a record zT of 2.6 at 850 K in Cu 2 Se-CuInSe 2 composites. It was suggested that the incorporation of a small fraction of In into the Cu 2 Se lattice induced partial localization of Cu + ions, and a hybrid structure with same Se lattice was formed.…”
Section: Liquid-like or Superionic Materialsmentioning
confidence: 99%
“…3a, Cu 2 Se possesses two sublattices: the rigid FCC framework of Se atoms and the disordered and flowing sublattice of Cu. At high temperatures, Cu ions migrate from one site (interstitial one formed by Se) to another, exhibiting a flowing character that is Figure 1 Timeline of zT for selected Cu-based superionic conductors [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] (red), tetragonal [28][29][30][31][32][33][34][35][36][37] (blue) and distorted [38][39][40][41][42][43][44][45][46][47][48][49] (green) diamond-like materials and BiCuSeO oxyselenides (purple) [50][51][52][53][54][55][56][57][58][59]…”
Section: Decoupled Transport Properties By Two Independent Sublatticesmentioning
confidence: 99%
See 1 more Smart Citation
“…(ZT values of 1.7-1.9 for Cu 2−x S [12][13][14][15][16][17][18], 1.3-2.1 for Cu 2−x Se [14][15][16][17], and 0.3-1.1 for Cu 2−x Te [18][19][20]). Chemical doping has been widely adopted to tune the carrier concentration and improve the ZT of thermoelectric materials [21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%